Wacana Feminisme dalam Catatan Najwa Spesial Hari Kartini - Agung Drajat Sucipto (Kalijaga Journal of Communication, 2020)
This study aims to find the representation of feminist discourse in the Najwa Notes program entitled “Women in the Shihab Family”. The Shihab family is known as a family that has a high level of religious knowledge with the figure of M. Quraish Shihab in it. The negative stigma against women, which is always associated with religious narratives, is an important point to see how women from the Shihab family view freedom. The aspect of freedom in this event is illustrated by the motive for this event, namely as a reflection of Kartini Day, which is known as the inspiration for the rise of women in a patriarchal culture. This study uses a qualitative method with a feminist discourse approach to Sara Mills. This research found that women in the Shihab family uphold the principle of independence without sacrificing their duties in the domestic sphere. For them, women need to have self-confidence, be able to make their own decisions, be empowered to be able to overcome obstacles in themselves to progress, and be of benefit to those around them. This narrative then deliberately provided stimulation for women in Indonesia who became the object of the story of the women of the Shihab family. Readers who are in the wider community are given the doctrine of freedom through joint production efforts between the writer and the reader so that they are indoctrinated to believe in and apply the messages contained in the program.Penelitian ini bertujuan untuk menemukan representasi wacana feminis dalam acara Catatan Najwa dengan tajuk “Perempuan di Keluarga Shihab”. Keluarga Shihab dikenal sebagai keluarga yang memiliki tingkat pengetahuan agama yang tinggi dengan figur M. Quraish Shihab di dalamnya. Stigma negatif terhadap perempuan yang selalu di relasikan dengan narasi-narasi keagmaan, menjadi point penting untuk melihat bagaimana perempuan dari keluarga Shihab memandang kebebasan. Aspek kebebasan dalam acara ini tergambar dari motif acara ini dibuat, yakni sebagai refleksi hari Kartini, yang dikenal sebagai inspirator kebangkitan perempuan dalam budaya patriarki. Penelitian ini menggunakan metode kualitatif dengan pendekatan wacana feminisme Sara Mills. Penelitian ini menemukan bahwa perempuan di keluarga Shihab memegang teguh prinsip kemandirian tanpa mengkorbankan tugas-tugas mereka di wilayah domestik. Bagi mereka, perempuan perlu memiliki sifat percaya diri, mampu membuat keputusan sendiri, berdaya untuk bisa mengalahkan hambatan pada dirinya untuk maju dan bermanfaat bagi sekelilingnya. Narasi ini kemudian secara sengaja memberikan stimulis bagi para perempuan di Indonesia yang dijadikan objek dengan subjek penceritaan para perempuan keluarga Shihab. Pembaca yang merupakan masyarakat luas diberikan doktrin kebebasan melalui upaya produksi bersama antara penulis dengan pemabaca, sehingga mereka didoktrinasi untuk meyakini dan mengaplikasikan pesan yang terkandung dalam acara.